Behavior of seismic wave propagation with respect to fracture orientations in limestone, Perak, Malaysia - Masyhur, Eko March Handoko Bin; Rafek, Abdul Ghani Abd; Noh, Khairul Arifin Mohd (International Journal of Engineering and Technology, 2018)
Conventional shallow surface seismic refraction survey is associated with long elastic wavelength thus it is often ignoring the existence of cracks and fractures underneath.Â Fracture has essential effect on reducing seismic velocity.Â This paper highlights the velocity variation in different direction with respect to preferred orientation of fracture sets of limestone in a quarry located at Chemor, Perak, Malaysia.Â Multi azimuth seismic refraction survey in the orientation of fan shooting is utilized to records seismic velocity from different azimuth.Â Slowness concept is used to study the responses of seismic wave velocity in regards to the discontinuity orientation.Â The analysis of the results indicate seismic wave propagates faster in the direction parallel with the strike of the fracture.Â The seismic wave experience largest time delay as the wave propagates perpendicular with the strike direction of the fracture structure.Â With this behavior of seismic wave in respect to the fractures orientation, it is possible to map the extension of the orientation of subsurface fractures.